Clinical Benefit of Antiviral Agents for Hepatocellular Carcinoma Patients With Low Preoperative HBV-DNA Loads Undergoing Curative Resection: A Meta-Analysis - Liu, Kai-Xuan; Hong, Jian-Guo; Wu, Rui; Dong, Zhao-Ru; Yang, Ya-Fei; Yan, Yu-Chuan; Yang, Chun-Cheng; Yan, Lun-Jie; Yao, Sheng-Yu; Li, Hai-Chao; Zhi, Xu-Ting; Li, Tao (Frontiers in Oncology, 2021)
Background & Aims: The clinical benefit of adjuvant antiviral therapy after curative therapy for HCC in patients with high preoperative HBV-DNA loads has been studied widely but that in patients with low preoperative HBV-DNA loads remains controversial. The purpose of this study was to determine the effect of antiviral treatment prophylaxis on HBV reactivation, overall survival (OS), and postoperative liver function in patients with low preoperative HBV-DNA levels undergoing curative resection. Methods: A meta-analysis was conducted by searching Web of Science, PubMed, Embase, and Cochrane Library until May 2020. We used REVMAN for data analysis and completed the study under the PRISMA guidelines. Results: Three randomized trials and seven cohort studies, comprising of 1131 individuals, were included in the meta-analysis. Antiviral treatment significantly reduced the rate of HBV reactivation after curative treatment of HCC, with a pooled risk ratio of 0.12 (95 percent c.i. 0.07 to 0.21; P＜0.00001). The trials were consistently favorable for the antiviral group, with a pooled hazard ratio of 0.52 (95 percent c.i. 0.37 to 0.74; P =0.0002) in respect of OS rate. However, by pooling the data from studies that reported ALT on the 30th day postoperatively, the result didn't reach statistical significance (mean difference -4.38, 95 percent c.i. -13.83 to 5.07; P= 0.36). The I² values of the heterogeneity test for the above three comparisons are zero. Conclusion: Antiviral therapy during curative resection is effective in reducing HBV reactivation and improving OS rate in HCC patients with low viral load.